2019
DOI: 10.3390/su11092486
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on Heat Transfer and Strength Analysis of Backfill with Ice Grains in Deep Mines

Abstract: In deep mines, two urgent problems are a high temperature thermal environment and solid waste. Filling the goaf with slurry mixed with ice grains is an effective way to solve these two problems simultaneously. The thermal property and mechanical property of the ice-added backfill have a great influence on the cooling effect in the deep mine. In this study, an experimental facility for measuring the temperature distribution of ice-added backfill slurry was established, and the temperature of backfill slurry wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 27 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Zhang et al experimentally studied the distribution law of the internal temperature inside the ice-filled slurry, and the results showed that the mechanical properties of the ice-filled slurry backfill were enhanced to a certain extent. e addition of PCM will affect the compressive strength thermal conductivity and the specific heat capacity [13,14]. Wang et al used CFD simulation and experiment to study the temperature distribution characteristics in the ice-filled filling body, thus verifying the consistency of simulation and experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al experimentally studied the distribution law of the internal temperature inside the ice-filled slurry, and the results showed that the mechanical properties of the ice-filled slurry backfill were enhanced to a certain extent. e addition of PCM will affect the compressive strength thermal conductivity and the specific heat capacity [13,14]. Wang et al used CFD simulation and experiment to study the temperature distribution characteristics in the ice-filled filling body, thus verifying the consistency of simulation and experiment.…”
Section: Introductionmentioning
confidence: 99%
“…The deeper the mining depth, the higher the temperature of surrounding rock, and the more serious the thermal hazard. In many countries, thermal hazard in mines appears one after another [5][6][7][8]. In South Africa, gold mines are about 2800 m deep and the temperature of rock reaches 75 • C, whereas the Mponeng gold mine is about 4100 m deep and the temperature of rock reaches 66 • C. In Japan, the Chang-pan coal mines rock temperature reaches 42-48 • C and the water temperature reaches 72 • C. In the Feng-yu lead-zinc mine in Hokkaido, the temperature of rock reaches 69-130 • C. The average geothermal temperature per kilometer is 30-40 • C in Russia, with individual areas reaching 52 • C. In India, where gold mine are about 3000 m deep, the geothermal temperature reaches 70 • C. In China, some mines are one km deep, the rock temperature has exceeded 50 • C. In addition, many countries (e.g., Zambia, Mexico, Nicaragua, Poland, Germany) have thermal hazards in mines.…”
Section: Introductionmentioning
confidence: 99%
“…The deeper the mining depth, the higher the temperature of surrounding rock, and the more serious the thermal hazard. In many countries, thermal hazard in mines appears one after another [5][6][7][8]. In South Africa, gold mines are about 2800 m deep and the temperature of rock reaches 75 °C, whereas the Mponeng gold mine is about 4100 m deep and the temperature of rock reaches 66 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The virgin rock temperature rises with mining depth [6]. The heat of the surrounding rocks is transferred to the airflow because of the large temperature difference between them, and the thermal environment of the mines continues to deteriorate [7][8][9]. Heat damage then inevitably occurs.…”
Section: Introductionmentioning
confidence: 99%